Addressing Logistical Barriers to Childhood Vaccination Using an Automated Reminder System and Online Resource Intervention: A Randomized Controlled Trial - Wagner, Nicole M. (Vaccine, 2021)
BACKGROUND: As the rates of vaccination decline in children with logistical barriers to vaccination, new strategies to increase vaccination are needed. The goal of this study was to develop and evaluate the effectiveness of the Vaccines For Babies (VFB) intervention, an automated reminder system with online resources to address logistical barriers to vaccination in caregivers of children enrolled in an integrated healthcare system. Effectiveness was evaluated in a randomized controlled trial. METHODS: Qualitative interviews were conducted with parents of children less than two years old to identify logistical barriers to vaccination that were used to develop the VFB intervention. VFB included automated reminders to schedule the 6- and 12-month vaccine visit linking caregivers to resources to address logistic barriers, sent to the preferred mode of outreach (text, email, and/or phone). Parents of children between 3 and 10 months of age with indicators of logistical barriers to vaccination were randomized to receive VFB or usual well child care (UC). The primary outcome was percentage of days undervaccinated at 2 years of life. A difference in differences analysis was conducted. RESULTS: Qualitative interviews with 6 parents of children less than 2 years of age identified transportation, scheduling challenges, and knowledge of vaccine timing as logistical barriers to vaccination. We enrolled 250 participants in the trial, 45% were loss to follow-up. There were no significant differences in vaccination uptake between those enrolled in UC or the VFB intervention (0.51%, p=0.86). In Medicaid enrolled participants, there was a modest decrease in percentage of days undervaccinated in the VFB intervention compared to UC (6.3%, p=0.07). CONCLUSION: Automated Reminders and with links to heath system resources was not shown to increase infant vaccination uptake demonstrating additional resources are needed to address the needs of caregivers experiencing logistical barriers to vaccination.